Services Trade Restrictiveness Index (STRI): Transport and Courier Services - Geloso Grosso, Massimo (OECD Publishing, 2014)
This paper presents the services trade restrictiveness indices (STRIs) for transport and courier services. The STRIs are composite indices taking values between zero and one, zero representing an open market and one a market completely closed to foreign services providers. The indices are calculated for 40 countries, the 34 OECD members and Brazil, China, India, Indonesia, Russia and South Africa. This report presents the first vintage of indicators for transport and courier services and captures de jure regulations in force in 2013. The STRI supports the view that these services are subject to very different regulatory frameworks and, in some cases, to a relatively elevated degree of regulation. Indices for air transport covering measures affecting commercial establishment and accompanying movement of natural persons are on average quite high (0.43), with little variation across countries.
Keywords: Trade